2017
DOI: 10.1108/aaaj-11-2015-2291
|View full text |Cite
|
Sign up to set email alerts
|

Structure of intellectual capital – an international comparison

Abstract: Purpose Academics and practitioners around the world have shown interest in what constitutes the relevant intellectual capital (IC) in firms. However, studies have largely neglected to examine whether IC has identical or different structural elements in various parts of the world. The purpose of this paper is to suggest that country-specific institutional structures may impact the perception of IC, and empirically analyse whether differences exist between five countries drawing on the institutional theory. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(107 citation statements)
references
References 110 publications
1
95
0
Order By: Relevance
“…The production of ambiguous results can be due to the IC contributions' differing by sector, industry, typology, firm size, and by knowledge management practices (Bontis et al, ; Chuang, Chen, & Chuang, ; Inkinen, Kianto, Vanhala, & Ritala, ; Kianto et al, ). In fact, there are elements such as the reference context (social, environmental, cultural, and economic), the sector of activities and differences in the technology intensity that can influence and/or moderate the efficient and effective management of intangible assets on the processes of value creation (Reed, Lubatkin, & Srinivasan, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The production of ambiguous results can be due to the IC contributions' differing by sector, industry, typology, firm size, and by knowledge management practices (Bontis et al, ; Chuang, Chen, & Chuang, ; Inkinen, Kianto, Vanhala, & Ritala, ; Kianto et al, ). In fact, there are elements such as the reference context (social, environmental, cultural, and economic), the sector of activities and differences in the technology intensity that can influence and/or moderate the efficient and effective management of intangible assets on the processes of value creation (Reed, Lubatkin, & Srinivasan, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is a consequence of the existence of two separate streams of literature about knowledge, and the conceptual and empirical ambiguity caused by this separation (Kianto et al, 2014). While IC literature examines the certain type of knowledge as a stock, or "capital" in a given point of time (Edvinsson and Malone, 1997;Inkinen, 2015;Inkinen et al, 2017), KM literature concentrates on the knowledge-related processes and practices to manage and control knowledge-based resources (Heisig, 2009;Inkinen et al, 2015;Hussinki et al, 2017). These two streams of literature reflect "static" and "dynamic" interpretations of knowledge (Kianto et al, 2014), knowledge-based resources (Brooking, 1996;Stewart, 1997) and knowledge-based capabilities (Teece et al, 1997;Teece, 2007), "know-that" (declarative knowledge) and "know-how" (procedural knowledge), as suggested by Kogut and Zander (1992).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Sharma and Dharni's (2016) observed that the majority of research studies conducted in the USA, UK and France establish a negative relationship between the IA and performance of the firm. Other research found no relationship between performance and region and in a research on whether the IC value was perceived differently across nations, Inkinen et al (2017) proved the similarity of IC elements across the examined countries, establishing that firms are starting to uniform IC management, and therefore, verify less variation at this level.…”
Section: Theoretical Backgroundmentioning
confidence: 90%